UJI METODE INOKULASI DAN PATOGENISITAS BLOOD DISEASE BACTERIUM (BDB) PADA BUAH PISANG (Musa Sp.) - Ratri Kusuma Devi; Luqman Qurata Aini; Abdul Latief Abadi (Universitas Brawijaya, 2013)
This study aims to examine several inoculation methods for pathogenisity test ofBDB on banana fruit. The Results showed that injection method and smearingsuspension bacteria using cotton bud on the base of fruit was capable in producingsymptoms of blood disease on banana fruit. The injection method is shown to bethe most effective method because it caused blood disease symptoms in thebanana fruit at the first day after inoculation. Inoculums densities of 108 and 109CFU/ml of BDB could develop disease on third and sixth day after inoculation.BDB produced unique symptoms by causing yellowing and browning on the fleshof a banana fruit as well as browning at the fruit placenta in 7 days afterinoculation, the symptom is different with caused by other pathogen like asXanthomonas oryzae, Pantoea sp dan Erwinia carotovora, dan Ralstoniasolanacearum.Keywords: banana, Blood Disease Bacterium (BDB), inoculation